Soil manganese dynamics and its uptake in wheat (Triticum aestivum) influenced by chloride and manganese application - NARENDER NARENDER; R S MALIK (The Indian Journal of Agricultural Sciences, 2018)
Manganese (Mn) is one of the essential micro-nutrients having an important contribution in paddy (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping systems. Wheat is an important cereal crop of Haryana State and is highly susceptible to Mn deficiency. During submerged paddy, solubility of Mn increases appreciably because of its reduction and continuous leaching from upper to lower soil layers which in turn results in its deficiency in the succeeding winter season crops especially wheat. Often, Mn fertilization under salinity stress is of main concern to be investigate, especially in arid and semi-arid regions of Haryana. So, in order to evaluate soil manganese dynamics and its uptake in wheat influenced by chloride (Cl-) and Mn application, laboratory as well as a screen house experiment was conducted at CCS HAU, Hisar, Haryana. Results revealed that a decreased grain and straw yield and Mn uptake in wheat with graded doses of Cl- application. The highest grain and straw yield of wheat were recorded with 25mg Mn/kg and without chloride application. However, maximum Mn content and its uptake in wheat was recorded under treatment of 50 mg Mn/kg. Among all Mn fractions in post-harvest soils, maximum Mn was associated with residual (RES) fraction followed by MnOX > AFeOX > CFeOX > EX > CARB > OM fractions. Organic matter bound (OM) showed a very little amount of Mn content due to low content of organic carbon in experimental soil. Thus, chloride application along with Mn fertilizers showed antagonistic effect on wheat yield and its uptake as well as Mn dynamics in soil.